From Manuscripts to Moderation: Sundanese Wisdom in Countering Religious Radicalism - Jaeni, Muhamad; Fathudin, Ahmad Ubaedi; Burhan, Ali; Huda, Moh. Nurul; Aini, Rofiqotul (UIN Sunan Gunung Djati Bandung, 2023)
Deradicalization has been a topic of interest among writers since the 19th century, when religious radicalism began to spread in the Islamic world. Tubagus Ahmad Bakri (TAB) wrote numerous religious texts against religious radicalism. His writings have contributed to developing a harmonious and tolerant social religious order. This writing attempts to map out the religious deradicalization concepts in the writings of Sundanese religious figures who made efforts to develop a comprehensive and tolerant religious ideology. This study shows how the Sundanese manuscripts have contributed to developing a moderate religious ideology that rejects radical religious texts and sets in motion an anti-radicalism social movement in the community. Employing the critical discourse analysis method, this study has revealed that TAB’s religious writings contain three important elements that counter religious radicalism: First, the importance of religious tolerance, the need for moderate religious understanding, and strong adherence to local wisdom. Second, rejection of radical religious texts, such as texts that prohibit having a madhhab, prohibition of istighasa, and declare making a pilgrimage to tombs as a misguided practice. Third, social commitment to religious moderation is marked by a movement of writing and translating religious books, community learning, and anti-radicalism campaign through community religious studies.